2015
DOI: 10.1007/s11663-015-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Na2O on the Solidification and Crystallization Behavior of CaO-SiO2-Al2O3-Based Mold Flux

Abstract: The reaction between [Al] and SiO 2 sharply increased the Al 2 O 3 and decreased SiO 2 contents in mold flux during the continuous casting of high-Al steels. These changes converted original CaO-SiO 2 -based flux into CaO-SiO 2 -Al 2 O 3 -based flux, promoting the crystallization and deteriorating the mold lubrication. Therefore, study on the solidification and crystallization behavior of CaO-SiO 2 -Al 2 O 3 -based mold flux, with the applicable fluidizers, is of importance. The effect of Na 2 O, predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…This means that microstructure of the mold fluxes containing higher content Al 2 O 3 can easily change and crystallize under proper temperatures if compared with CaO–SiO 2 mold fluxes. This could be an important cause of why mold fluxes containing high content Al 2 O 3 have a shorter incubation time of crystallization and stronger crystallization tendency that is easy to deteriorate the mold lubrication . Hence, the structural characteristics of high‐Al steels mold fluxes must be considered during the design process, which could adjust the performance to meet the demands of high‐Al steels casting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This means that microstructure of the mold fluxes containing higher content Al 2 O 3 can easily change and crystallize under proper temperatures if compared with CaO–SiO 2 mold fluxes. This could be an important cause of why mold fluxes containing high content Al 2 O 3 have a shorter incubation time of crystallization and stronger crystallization tendency that is easy to deteriorate the mold lubrication . Hence, the structural characteristics of high‐Al steels mold fluxes must be considered during the design process, which could adjust the performance to meet the demands of high‐Al steels casting.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, advanced high‐Al steels, including the twin‐induced plasticity and transformation‐induced plasticity steels, have gained tremendous interests due to their high performances, such as the extraordinary ductilities and the high tensile strengths. These new grades of steel are characterized by the presence of high concentrations of Al (0.5%–2.5%) in the molten steel that yields improved mechanical properties and decreased weights of the final steel products . However, alloying elements‐based Al usually react with the conventional CaO–SiO 2 mold flux to induce mold fluxes with contents poor in SiO 2 and rich in Al 2 O 3, hence converting the original CaO–SiO 2 mold fluxes into CaO–SiO 2 –Al 2 O 3 mold fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature was maintained for 5 min to observe whether crystals could form in the molten slags. Some researchers [21] showed that the residence time of mold powders in the mold was approximately 5 min.…”
Section: Methodsmentioning
confidence: 99%